Babywatching - Morris, Desmond (New York Crown Publishers, 1992)
The author provides direct, concise answers to such questions as Why does a baby have a soft spot on its head?; How well can babies see?; Are babies intelligent?; Why was the stork said to bring babies?; and Why does the proud father hand out cigars when his baby is born?
Include Illustrations and Index
Keywords: Infants--Development -- Infants